Anterior pushing technique for a broken scalpel blade in lumbar discectomy: a case report - Čeleš, Dejan; Gasparini, Mladen; Mohar, Janez (Frontiers in Surgery, 2023)
The presence of broken surgical blades or other surgically uncontrolled sharp and pointed objects in the disc space is a rare but potentially severe complication of posterior lumbar spine procedures. Herein, we report the case of a 59-year-old female patient with a history of lumbar decompression and interspinous process device implantation who underwent an instrumented revision of the lumbosacral junction. During the L5–S1 discectomy, the scalpel blade broke, and the broken fragment could not be retrieved through the posterior approach. With regard to the vascular anatomy, we partially pushed the fragment through the anterior annulus into the retroperitoneal space. In addition, pedicle screws were locked to ensure the stability of the construct. The fractured blade fragment was eventually removed by laparoscopy 1 week after the initial procedure. This experience suggests that the anterior pushing technique with fluoroscopy is an option in rare cases where a broken scalpel blade cannot be reached through the posterior approach. In such cases, computed tomography angiography is recommended.